The novels of Uladzimir Karatkevich in the 1960–80s (critical assessment, genre and style innovation) - Lappo, Maryia S. (Journal of the Belarusian State University. Philology, 2019)
The article is devoted to the novels of U. Karatkevich in the literary-historical context of the 1960–80s, taking into account the characteristics of the literature development process in Belarus. The first part of the article deals with the li- terature development process in the specified period and with the reviews and analytical works written about the U. Karatkevich’s novels in the 1960–80s. The first stage of the U. Karatkevich’s literary career (1960–70s) is characterized by the ambiguous researchers’ reaction to the novels. Later the writer’s status has transformed into a more «recognized» and «authoritative»; and works about the novels have changed from the evaluation (acceptance/non-acceptance) to the analysis (analysis of the writer’s style, comparative and culturological research). The second part of the article is about the theme and style innovations of the U. Karatkevich’s novels in the context of the Belarusian prose development. It is stressed that the distinguishing feature of the novels is genre and stylistic synthetism. The main innovation of U. Karatkevich’s works is connected with the author’s decision to present conceptualized events of Belarusian history, not the realities of the XX century.